ß-Alanine supplementation in combat sports: evaluation of sports performance, perception, and anthropometric parameters and biochemical markers—a systematic review of clinical trials - Fernández-Lázaro, D.; Fiandor, E. M.; García, J. F.; Busto, N.; Santamaría-Peláez, M.; Gutiérrez-Abejón, E.; Roche, E.; Mielgo-Ayuso, J. (Nutrients, 2023)
ß-alanine does not have an ergogenic effect by itself, but it does as a precursor for the synthesis of carnosine in human skeletal muscle. ß-alanine and carnosine together help improve the muscles` functionality, especially in high-intensity exercises such as combat sports. Therefore, ß-alanine could be considered a nutritional ergogenic aid to improve sports performance in combat athletes. We aimed to critically review clinical trial evidence on the impact of ß-alanine supplementation on sports performance, perception, and anthropometric parameters, as well as circulating biochemical markers in combat athletes. This systematic review was conducted following the specific methodological guidelines of the Preferred Report Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA), the PICOS question model, the Critical Review Form of McMaster, and the PEDro scale. Furthermore, the Cochrane risk-of-bias assessment tool was used. The search was carried out in the SCOPUS, Web of Science (WOS), and Medline (PubMed) databases for studies published from the beginning of the database until July 31, 2023. Of the 41 registers identified, only 7 met the established criteria and were included in this systematic review. Overall, performance parameters related to strength, power, total exercise work capacity, and combat-specific parameters were significantly improved (p < 0.05). Perception parameters increased non-significantly (p > 0.05). Regarding biochemical parameters, carnosine increased significantly (p < 0.05), pH decreased non-significantly (p > 0.05), and the results for blood bicarbonate and blood lactate were heterogeneous. Finally, there was a non-significant (p > 0.05) improvement in the anthropometric parameters of lean mass and fat mass. ß-alanine supplementation appears to be safe and could be a suitable nutritional ergogenic aid for combat athletes.